2020
DOI: 10.1111/nyas.14492
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal cancer surgery: review of complications and their management

Abstract: Esophagectomy, even with the progress in surgical technique and perioperative management, is a highly specialized surgery, associated with a high rate of complications. Early recognition and adequate treatment should be a standard of care for the most common postoperative complications: anastomotic leakage, pneumonia, atrial fibrillation, chylothorax, and recurrent laryngeal nerve palsy. Recent progress in endoscopy with vacuum and stent placement, or in radiology with embolization, has changed the management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 112 publications
0
30
0
Order By: Relevance
“…Although the incidence of PPCs can be reduced by MIE, persuading patients to quit smoking before surgery, exercising respiratory related muscles before surgery, and relieving postoperative wound pain 27 , there is still lack of a readily available model that can effectively predict the incidence of PPCs. In this study, we nally found that smoking index, AFR, ASA physical status , and recurrent laryngeal nerve palsy were independent risk factors for PPCs in patients with esophageal cancer using univariate and multivariate logistic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the incidence of PPCs can be reduced by MIE, persuading patients to quit smoking before surgery, exercising respiratory related muscles before surgery, and relieving postoperative wound pain 27 , there is still lack of a readily available model that can effectively predict the incidence of PPCs. In this study, we nally found that smoking index, AFR, ASA physical status , and recurrent laryngeal nerve palsy were independent risk factors for PPCs in patients with esophageal cancer using univariate and multivariate logistic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Plenty of studies have demonstrated that current smoking status is associated with PPCs 36 , and smoking cessation decrease the incidence of PPCs 27,37 . But none of these studies seemed to include smoking index that re ects the degree of smoking rather than the status of smoking in some aspect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic treatment, endoluminal stenting, and vacuum therapy are among the most common strategies. A recent meta-analysis compared endoscopic techniques and vacuum therapy and demonstrated that vacuum with sponge provides a higher success rate for leak resolution with shorter hospital stays [ 14 , 15 ]. In the case evaluated here, sponge vacuum treatment played an essential role in the resolution of the complication.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with esophageal cancer, esophagectomy remains the primary option for esophageal cancer patients because of removing the tumors of the esophagus and improving symptoms. Despite the incidence and mortality of esophageal cancer decline resulting from medical advances and perioperative management, postoperative pulmonary complications, especially postoperative pulmonary infection (POI), which is a principle problem associated with patient's prognosis and outcomes [4]. Several studies reported that POI occurred in almost 16%-40% of EC patients and has been identified to be a factor for perioperative death and long-term survival [5][6][7].…”
Section: Introductionmentioning
confidence: 99%